2022
DOI: 10.1159/000528537
|View full text |Cite
|
Sign up to set email alerts
|

Proton Beam Therapy versus Radiofrequency Ablation for Patients with Treatment-Naïve Single Hepatocellular Carcinoma: A Propensity Score Analysis

Abstract: Introduction: Proton beam therapy (PBT) is known to be an effective locoregional treatment for hepatocellular carcinoma (HCC). However, few comparative studies in treatment-naïve cases have been reported. The aim of this study was to compare the survival outcomes of PBT with those of radiofrequency ablation (RFA) in patients with treatment-naïve solitary HCC. Methods: Ninety-five consecutive patients with treatment-naïve HCC, a single nodule measuring ≤5 cm in diameter, and a Child-Pugh score of ≤8 who were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…Previous studies of HCC have found 3-year LC and OS rates of 91-96% and 67-73% with SBRT [2][3][4]14,15], and 79.9-90% and 56-77.8% with PBT [5][6][7][16][17][18]. Thus, our 3-year LC and OS rates of 86.3% and 51.9% are similar to these reports.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies of HCC have found 3-year LC and OS rates of 91-96% and 67-73% with SBRT [2][3][4]14,15], and 79.9-90% and 56-77.8% with PBT [5][6][7][16][17][18]. Thus, our 3-year LC and OS rates of 86.3% and 51.9% are similar to these reports.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, PBT could make the dose concentration threshold for a tumor and have a lower dose for a normal liver than photon therapy [36]. However, many reports comparing PBT and other treatments were retrospective studies [17,[37][38][39][40], and there was a report which investigated operable or ablation-treatable HCC [41]. Gradually, randomized comparative trials between PBT and other treatments are being reported [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis, local control was similar regardless of definitive or palliative irradiation (Vp3 and Vp4), but the OS rate was clearly worse in palliative cases. This indicates that outcomes depend on the patient’s background, as found previously [ 43 , 44 ]. Multivariate analysis also showed a trend for a relationship between PS and liver function with OS.…”
Section: Discussionsupporting
confidence: 78%